Efektivitas Penegakan Undang-Undang Penghapusan Kekerasan Dalam Rumah Tangga Nomor 23 Tahun 2004 Di Yogyakarta - Dika Pratama (Universitas Islam Indonesia, 2019)
This study aims to determine the level of effectiveness of law enforcement contained in the Law on the Elimination of Domestic Violence Number 23 of 2004 (PKDRT Law) in Yogyakarta. Starting in terms of law enforcement officers, the community and also studies of the PKDRT Law on whether it has been running as expected or there are still obstacles that may cause the law has not been running optimally. The type of research used in this study is sociological-juridical research, namely in dealing with the problems that are discussed based on applicable regulations and then associated with the facts that occur in society. In supporting and completing the secondary data, field research is conducted to obtain the primary data. This study concludes, the effectiveness of the Domestic Violence Act in terms of preventing the occurrence of domestic violence is still hampered by several causes, namely: the focus of the Domestic Violence Act is still focused on the mere enforcement dimension, prevention is still partial, and socialization is not accompanied by rapid response.